Clinical Outcome of Drug-Eluted Stenting (Zilver PTX) in Patients With Femoropopliteal Occlusive Disease a Single Center Experience. (June 2022) - AbuRahma, Ali F.; Beasley, Matthew; AbuRahma, Zachary T.; Davis, Meghan; Adams, Elliot; Dean, L. Scott; Shapiro, Jake; Scott, Grant; Davis, Elaine
Background: Few industry sponsored trials reported satisfactory outcomes in the use of drug-eluting stents (DES) for treatment of femoropopliteal arterial disease. This study analyzed the early/late clinical outcome from a real world single center. Patient Populations/Methods: A total of 115 limbs treated with Zilver PTX were analyzed for: major adverse limb event (MALE: above ankle limb amputation/major intervention at 1 year), major adverse events (MAEs; death, amputation, and target lesion thrombosis/reintervention), primary patency (based on duplex ultrasound ± ankle brachial indexes), limb salvage, and amputation free survival rates (AFS) at 1 and 2 years. Results: Indications included claudication in 32% and critical limb threatening ischemia (CLTI) in 68%. Lesions treated included: superficial femoral artery (SFA) 66%, both SFA and popliteal artery (PA) 19% and PA 15%. Mean lesion length was 21 cm and 68% had total occlusion. 45% were Trans-Atlantic Inter-Society Consensus (TASC) TASC II D lesions and 55% A–C lesions. Mean follow-up was 18.4 months (1–76 months). Perioperative major morbidity rate was 8.7% with 0% mortality. MALE rate at 1 year was 17% (13.5% for claudication vs 19.2% for CLTI, p=0.4499). MAE rate was 30% for claudication versus 52% for CLTI (p=0.0392). Overall primary patency rates at 1 and 2 years were 75% and 54% (86% and 71% for claudication vs 70% and 46% for CLTI, respectively, p=0.0213). Primary patency rates at 1 and 2 years were 94% and 88% for TASC A-C lesions versus 50% and 16% for TASC D lesions (p<0.0001). Overall freedom from MALE rate at 1 and 2 years were 85% and 79% (86% and 86% for claudication vs 84% and 74% for CLTI, p=0.2391). These rates were 96% and 93% for TASC A-C lesions versus 70% and 50% for D lesions, respectively (p<0.0001). Limb salvage rates at 1 and 2 years were 93% and 86% (100% and 100% for claudication vs 89% and 78% for CLTI, p=0.012). Overall AFS rates at 1 and 2 years were 79% and 71% (93% and 82% for TASC A–C vs 59% and 59% for D lesions, p=0.001). Conclusion: Clinical outcomes after DES (Zilver PTX) in femoropopliteal arterial lesions were satisfactory for TASC A–C lesions but inferior/unsatisfactory for TASC D lesions.